Gambaran Kadar Hemoglobin Pada Perokok Aktif Di Kayuagung Kabupaten OKI (Ogan Komering Ilir) Tahun 2024 - Fitri Aprianti; Ranti Liliana (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2024)
Smoking is one of the health problems because smoking is one of the main risk factors for several chronic diseases. The purpose of the study was to determine the description of hemoglobin levels in active smokers in Kayuagung, OKI Regency (Ogan Komering Ilir)) based on the duration of smoking and the degree of smoking. The research design used was quantitative descriptive with a proportionate stratified random sampling technique. The samples taken were 76 samples (15 primary data and 61 secondary data). The hemoglobin examination method was using the strip method (Easy Touch GCHb). Of the 76 samples, the results obtained were normal hemoglobin in 51 people (67%) and abnormal hemoglobin in 25 people (33%). Based on the duration of smoking ≤ 10 years, normal hemoglobin was 22 people (92%) and abnormal hemoglobin was 2 people (8%), while for the duration of smoking ≥ 10 years, normal hemoglobin was 29 people (56%) and abnormal hemoglobin was 23 people (44%). Based on the degree of smoking, the degree of light smoking has normal hemoglobin levels of 17 people (85%) and those who are not normal are 3 people (15%), the degree of moderate smoking has normal hemoglobin levels of 21 people (72%) and those who are not normal are 8 people (28%), and the degree of heavy smoking has normal hemoglobin levels of 13 people (48%) and those who are not normal are 14 people (52%). It is recommended that smokers can reduce smoking, maintain and regulate a healthy lifestyle.